Copper-Catalyzed Chan–Lam Cyclopropylation of Phenols and Azaheterocycles - Derosa, Joseph (J Org Chem, 2018)
Small molecules containing cyclopropane–heteroatom linkages are commonly needed in medicinal chemistry campaigns, yet are problematic to prepare using existing methods. To address this issue, a scalable Chan–Lam cyclopropylation reaction using potassium cyclopropyl trifluoroborate has been developed. With phenol nucleophiles, the reaction effects O-cyclopropylation, whereas with 2-pyridones, 2-hydroxybenzimidazoles, and 2-aminopyridines the reaction brings about N-cyclopropylation. The transformation is catalyzed by Cu(OAc)(2) and 1,10-phenanthroline and employs 1 atm O(2) as the terminal oxidant. This method is operationally convenient to perform and provides a simple, strategic disconnection toward the synthesis of cyclopropyl aryl ethers and cyclopropyl amine derivatives bearing an array of functional groups.